Water Management and Soil Fertility Status at A Reclaimed Tidal Lowland of Telang Jaya Village, South Sumatra, Indonesia - Bakri Bakri; Momon Sodik Imanudin; Wahyu L. Chandra (Journal of Wetlands Environmental Management, 2020)
Tidal lowland has a great prospect due to its vast area to support the improvement of national food security and the development of agribusiness system. Based on these potentials, it is necessary to study water management the physical dan chemical characteristics of soil on tidal land at Telang Jaya, South Sumatra. The aim of the study is to develop micro water management in the field level  for rice cultivation, and to evaluate the soil fertility in relation to the rice production.  The soil properties can be used to determine the level of soil fertility and the land management problem at the area. Research method was done by experimental research in combination with survey and monitoring. Rice was cultivated in tertiary block and the ground water table fluctuation was record in daily bases. Soil samples were taken from 0-20 cm depth (the root depth for common food crops) and then analyzed at the laboratory. The result had showed that the soil fertility status at Telang Jaya was low to moderate. The limiting factors of soil fertility found in this study were consisted of low nitrogent content, low C-organic content and acid soil condition (low bases and pH). Ground water taken at  February to March was maintained on 10 to (-10) cm related to the soil surface. It was sufficient for crop water requirement. Water management objective for second rice was mainaly for control drainage during the intial stage, and retain rainfall water. Pumping irrigation was required during Elnina climatic condition at generative phase. By proper water management system rice production could achive 5 ton/ha.